Methods of Engineering Culture of Prayer in Islamic Society Based on Revelation Exegesis - Saedeh Aghaei aghdam; mohammad سبحانی یامچی (پژوهش در آموزش معارف و تربیت اسلامی, 2023)
The purpose of the present study is to review methods of engineering culture of prayer in Islamic society based on revelation exegesis. The research method is descriptive-analytic and it has regarded the context and condition of revelation of verses and chapters of the Noble Qur’an and has also dealt with the most important strategies proposed by the Noble Qur’an to institutionalize the culture of prayer during the age of revelation. The results showed that God has initially started with introducing models, then he has raised people’s awareness by encouragement, discouragement, reverence, and storytelling. In the next stage, giving proposals, paving the ground, gradual gradation, perseverance, preservation, and so on are conducted. Of course, these methods can be adopted in rotation with any of the methods in the verses of the Noble Qur’an in appropriate conditions. From the first verses about the discussion of prayer in the Qur’an to the last chapters revealed in Medina, these methods have ever been visible in different ways (as it is noticeable in the review of verses). Furthermore, by consolidating commands in terms of prayer and institutionalizing its culture, we can make all cultural institutions in society achieve the most beautiful symbols and remove all ugly images from the realm of culture in human society without any historical limitation and with permanent and sustainable efficiency to pave the ground for improvement and passing the path of perfection.